The Relationship between VEGFC Gene Polymorphisms and Autoimmune Thyroiditis. (12th July 2022) - Gao, Chaoqun; Zhu, Jie; Qin, Qiu; Yang, Xiaorong; Jiang, Yanfei; Zhang, Jinan
Abstract : Background . Autoimmune thyroid diseases (AITDs), representative autoimmune diseases, mainly consist of Graves' disease (GD) and Hashimoto's thyroiditis (HT). In this passage, we investigated the association between vascular endothelial growth factor C (VEGFC) gene polymorphisms and AITDs. Methods . A total of 1084 patients with AITDs and 794 healthy controls were tested for VEGFC gene genotypes in four single nucleotide polymorphisms (SNPs) by high-throughput sequencing, and the correlation between VEGFC gene polymorphisms and AITDs was statistically analyzed. Results. The genotype distribution of rs3775194 was statistically associated with AITDs compared with the control group. Rs3775194 was associated with AITDs under the overdominant model, both before and after adjusting for confounding factors, while the other three SNPs were not associated with GD and HT. There was a prominent discrepancy between male healthy controls and male AITD patients under overdominant model in rs3775194 and the recessive model in rs11947611. The genotype distribution of rs3775194 was statistically related to male HT. Conclusion . These results reveal the correlation between VEGFC mutation and AITD susceptibility.